2020
DOI: 10.31234/osf.io/2raq7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of the Bodily Self: Effects of Visuomotor Synchrony and Visual Appearance on Virtual Embodiment in Children and Adults

Abstract: The sense of a bodily self is thought to depend on adaptive weighting and integration of bodily afferents and prior beliefs. Evidence from studies using paradigms such as the rubber hand illusion and full body illusion suggests changes in the integration of visuotactile bodily signals throughout childhood. Here, we extended this line of research by assessing how bottom-up visuomotor synchrony and expectancy, modulated by visual appearance of virtual avatars, contribute to embodiment in children. We compared re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…We report how we determined our sample size, all data exclusions, all manipulations and all measures in the study. All data, analysis code and research materials are available at [ 69 ]. Statistical analyses were performed in R v. 4.0.2 [ 70 ], and we used the lmerTest package [ 71 ] for the linear mixed model analyses.…”
Section: Methodsmentioning
confidence: 99%
“…We report how we determined our sample size, all data exclusions, all manipulations and all measures in the study. All data, analysis code and research materials are available at [ 69 ]. Statistical analyses were performed in R v. 4.0.2 [ 70 ], and we used the lmerTest package [ 71 ] for the linear mixed model analyses.…”
Section: Methodsmentioning
confidence: 99%
“…A significant concern of the present study is that we investigated only the short-term recovery process of bodily self-consciousness from a perturbation induced by visuomotor rotation. As stated in the introduction section, part of bodily self-consciousness is formed gradually through development (Riva, 2018;Weijs et al, 2020). Since our methods rely solely on motor learning paradigms, the time course of bodily self-consciousness formation that we can capture is limited to the short-term period that starts from its disruption to the completion of motor learning, which is typically less than an hour.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Ample evidence has suggested that body ownership and agency form over different time courses (Kalckert and Henrik Ehrsson, 2012;Keenaghan et al, 2020;Kokkinara et al, 2016;Kokkinara and Slater, 2014;Weijs et al, 2020). However, the theoretical underpinning of such time course differences is still unclear.…”
Section: Introductionmentioning
confidence: 99%